2014
DOI: 10.1371/journal.pone.0105318
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Brain Potentials during a Semantic Priming Task in Children with Learning Disabilities Not Otherwise Specified

Abstract: Learning disabilities (LDs) are the most common psychiatric disorders in children. LDs are classified either as “Specific” or “Learning Disorder Not Otherwise Specified”. An important hypothesis suggests a failure in general domain process (i.e., attention) that explains global academic deficiencies. The aim of this study was to evaluate event-related potential (ERP) patterns of LD Not Otherwise Specified children with respect to a control group. Forty-one children (8−10.6 years old) participated and performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 41 publications
6
11
0
Order By: Relevance
“…[ 26 ] Impaired attention shifting might be the reason for the poor performance of LD children in reading, writing, and arithmetic. [ 27 ] These findings support our results that both the ADHD + learning difficulties group and the pure ADHD group may have impaired inhibition and shifting functions.…”
Section: Discussionsupporting
confidence: 87%
“…[ 26 ] Impaired attention shifting might be the reason for the poor performance of LD children in reading, writing, and arithmetic. [ 27 ] These findings support our results that both the ADHD + learning difficulties group and the pure ADHD group may have impaired inhibition and shifting functions.…”
Section: Discussionsupporting
confidence: 87%
“…The paradoxical effect in ERPs has been observed only in pathological populations [63,64], but in our study, both groups were composed of healthy older adults. Hence, we suppose that the lack of LAN effect in the group with h-PA and the paradoxical LAN effect component at this latency in the group with l-PA might be a reflection of failures in the first processing stage mainly for the most complicated condition (i.e., disagreement).…”
Section: Electrophysiological Evidencementioning
confidence: 80%
“…It is often associated to a rapid allocation of attentional resources which can be mobilized for a variety of task goals such as the perception of threatening stimuli or successful memory encoding processes (Carretié et al, 2008 ; Olofsson et al, 2008 ; Schaefer et al, 2011 ). Reduced P2 amplitude, can also be associated with learning difficulties in reading, writing, and arithmetic domains (Fernández et al, 2014 ). In the current review, Kishiyama et al ( 2009 ) found no significant relationship between SES and P2 amplitude.…”
Section: Resultsmentioning
confidence: 99%